2015
DOI: 10.1590/0102-33062015abb0109
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis in Acrocomia aculeata Jacq. (Lodd.) ex Mart using the thin cell layer technique

Abstract: Considering the necessity of Acrocomia aculeata propagation for large-scale production, the aim of this study was to establish a somatic embryogenesis protocol using the thin cell layer (TCL) technique. Aerial parts of in vitro plants were transversally cut at the base into eight TCLs and placed in a culture medium for callus induction. The induction medium was composed of Y3 salts and Morel´s vitamins and supplemented with 150, 300 or 600 μM picloram. After 12 weeks the calli were transferred to a medium supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Due to its attractive features, the macaw palm domestication, genetic breeding and development of commercial plantations have encouraged financial investments in basic research, biotechnology and industry. Studies in several areas have been carried out with this purpose, including ecophysiology (Pires et al 2013), mating system (Lanes et al 2016), vegetative development (Berton et al 2013;Machado et al 2016), fruit development (Montoya et al 2016), phenotypic diversity (Ciconini et al 2013;Lanes et al 2015;Conceição et al 2015;Coser et al 2016) and biotechnological applications (Moura et al 2009;Luis and Scherwinski-Pereira 2014;Padilha et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its attractive features, the macaw palm domestication, genetic breeding and development of commercial plantations have encouraged financial investments in basic research, biotechnology and industry. Studies in several areas have been carried out with this purpose, including ecophysiology (Pires et al 2013), mating system (Lanes et al 2016), vegetative development (Berton et al 2013;Machado et al 2016), fruit development (Montoya et al 2016), phenotypic diversity (Ciconini et al 2013;Lanes et al 2015;Conceição et al 2015;Coser et al 2016) and biotechnological applications (Moura et al 2009;Luis and Scherwinski-Pereira 2014;Padilha et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Plastome sequences are also of great importance to understand evolutionary events in plants based on the knowledge of gene content, recombination events, loss of genes, gene transfer to the nucleus and genome rearrangements (Vieira et al 2016b;Bock 2017;Lopes et al 2017;Park et al 2017;Ruhlman et al 2017), as well as for plastid transformation aiming basic research (Rogalski et al 2006(Rogalski et al , 2008Alkatib et al 2012) and biotechnological applications (Daniell et al 2016;Zhang et al 2017) since the complete sequence of plastome is a prerequisite to choose target intergenic regions for insertion of transgenes and development of transplastomic plants (Daniell et al 2016;Fuentes et al 2017). The plastid transformation has been used efficiently for metabolic engineering (Daniell et al 2016;Fuentes et al 2017) and it is a viable alternative to manipulate plastid fatty acid biosynthesis (Rogalski and Carrer 2011) given that several efficient protocols of plant regeneration based on somatic embryogenesis are available for macaw palm (Moura et al 2009;Luis and Scherwinski-Pereira 2014;Padilha et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained for E. guineensis genotypes BRS C2328: On MS medium containing 0.6 µM ANA and 12.3 µM 2iP, 48% of the calli were embryogenic and 52.5% of them produced SEs (Silva et al, 2012). Likewise, in Acrocomia aculeata, Padilha et al (2015) observed friable calli in 53% of TCLs cultivated in Y3 culture medium supplemented with 75 µM Picloram and 12.5 µM 2iP. These results show the importance of auxin/cytokinin balance for embryogenic callus multiplication.…”
Section: Discussionmentioning
confidence: 62%
“…This technique has been used successfully for peach palm (Bactris gasipaes) (Steinmacher et al, 2007), Acrocomia aculeate (Padilha et al, 2015) and oil palm (E. guineensis) (Scherwinski-Pereira et al, 2010). This study was developed to address the need for multiplication and production of hybrid oil palm BRS Manicoré, aimed at more rapid production on a scale that meets national demand.…”
Section: Introductionmentioning
confidence: 99%
“…picloram associated with BAP or 2iP also induced the formation of embryogenic masses (Padilha et al, 2015).…”
Section: Discussionmentioning
confidence: 93%